Assessment of T1 Slope Minus Cervical Lordosis and C2‐7 Sagittal Vertical Axis Criteria of a Cervical Spine Deformity Classification System Using Long‐Term Follow‐up Data After Multilevel Posterior Cervical Fusion Surgery. Issue 1 (January 2019) - Hyun, Seung‐Jae; Han, Sanghyun; Kim, Ki‐Jeong; Jahng, Tae‐Ahn; Kim, Hyun‐Jib
Abstract : BACKGOUND: : Recently, previous research proposed a cervical spine deformity (CSD) classification using a modified Delphi approach. However, C2‐C7 sagittal vertical axis (SVA) and T1 slope minus C2‐C7 lordosis (TS−CL) cut‐off values for moderate and severe disability were based on expert opinion. OBJECTIVE: : To investigate the validity of a CSD classification system. METHODS: : From 2007 to 2012, 30 consecutive patients with a minimum 5‐yr follow‐up having 3‐ or more level posterior cervical fusion met inclusion criteria. The following radiographic parameters were measured: C0‐C2 lordosis, C2‐C7 lordosis, C2‐C7 SVA, T1 slope, and TS−CL. Pearson correlation coefficients were calculated between pairs of radiographic measures and health‐related quality of life. RESULTS: : Average follow‐up period was 7.3 yr. C2‐C7 SVA positively correlated with neck disability index (NDI) scores ( r = 0.554). Regression models predicted a threshold C2‐C7 SVA value of 40.8 mm and 70.6 mm correlated with moderate and severe disability based on the NDI score, respectively. The TS−CL had positive correlation with C2‐C7 SVA and NDI scores ( r = 0.841 and r = 0.625, respectively). Regression analyses revealed that a C2‐C7 SVA value of 40 mm and 70 mm corresponded to a TS−CL value of 20° and 25°, respectively. CONCLUSION: : Regression models predicted a threshold C2‐C7 SVA (value of 40.8 mm and 70.6 mm) and TS−CL (value of 20° and 25°) correlated with moderate and severe disability based on the NDI, respectively. The cut‐off value C2‐C7 SVA and TS−CL modifier of the CSD classification can be revised accordingly.